1997
DOI: 10.1063/1.118926
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet (340–390 nm), room temperature, photoluminescence from InAs nanocrystals embedded in SiO2 matrix

Abstract: InAs nanocrystals embedded in SiO2 matrix have been fabricated by a radio-frequency magnetron co-sputtering technique without postannealing. X-ray photoelectron spectra and Raman spectroscopy strongly suggest the existence of InAs nanocrystals in the SiO2 matrix. From the optical absorption spectrum, the absorption edge exhibits a very large blueshift of 3.3 eV with respect to that of bulk InAs. The double-peak ultraviolet photoluminescence is observed. Our experimental results show that this double-peak pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…12) InAs nanocrystals have been fabricated on SiO 2 =Si substrates by molecular beam epitaxy (MBE) 13) and in SiO x matrices by cosputtering. 14) However, luminescence from InAs QDs on SiO 2 films has not been clearly observed. In order to fabricate InAs QDs on an oxide film, InAs polycrystallinity should be suppressed on the oxide surface.…”
mentioning
confidence: 99%
“…12) InAs nanocrystals have been fabricated on SiO 2 =Si substrates by molecular beam epitaxy (MBE) 13) and in SiO x matrices by cosputtering. 14) However, luminescence from InAs QDs on SiO 2 films has not been clearly observed. In order to fabricate InAs QDs on an oxide film, InAs polycrystallinity should be suppressed on the oxide surface.…”
mentioning
confidence: 99%
“…Until now, many authors [33][34][35] reported that InAs quantum dots grown in the self-organized Stranski-Krastanov mode by metal organic vapor-phase epitaxy (MOVPE) or molecular beam epitaxy (MBE) exhibit a strong PL line peaking near 1.3 mm. Shi et al [8] reported the observation of ultraviolet (340-390 nm) PL from InAs nanocrystals embedded in SiO 2 films fabricated by cosputtering of InAs and SiO 2 . In this work, the near-infrared PL with peaks at 3.4 mm is observed for the first time.…”
Section: Pl Spectramentioning
confidence: 98%
“…Shi and Zhang et al fabricated some III-V semiconductors nanocrystals embedded in SiO 2 thin films by radio-frequency magnetron co-sputtering [3,[8][9][10][11][12][13][14][15], such as GaAs, InAs, InSb, InP, GaSb, In 0.2 G 0.8 As, InAs x P 1Àx , and Ga 1Àx In x Sb. A double-peak photoluminescence (PL) with peaks at 342 and 388 nm was observed in the InAs/SiO 2 composite thin film [8]. Kanemitsu and White et al also prepared some III-V semiconductors nanocrystals embedded in SiO 2 glass by sequential ion implantation and thermal annealing technique [1,[16][17][18] such as GaAs, GaN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…InAs nanocrystals have been fabricated on SiO 2 /Si substrate by molecular beam epitaxy (MBE) 17) and in SiO x matrix by co-sputtering technique. 18) However, luminescence from InAs QDs on the SiO 2 film has not been clearly observed. In order to fabricate InAs QDs on the oxide film, the InAs polycrystalline should be suppressed on the oxide surface.…”
Section: Introductionmentioning
confidence: 99%